The effect of religious practice on the prevalence of knee osteoarthritis - Surachai Chokkhanchitchai (2018)
The aim of this study is to evaluate the effect of religious practice on the prevalence, severity, and patterns of knee osteoarthritis (OA) in a Thai elderly population with the same ethnicity and culture but different religions. A house-to-house survey was conducted in two subdistricts of Phranakhon Sri Ayutthaya province where inhabitants are a mixture of Buddhists and Muslims. One hundred fifty-three Buddhists and 150 Muslims aged ≥ 50 years were evaluated demographically, physically, and radiographically. Those suffering knee pains were questioned about severity using the Western Ontario and McMaster University Osteoarthritis Index (WOMAC) scores and examined for their range of knee motion. Radiographic knee OA (ROA) was defined as Kellgren-Lawrence radiographic grade ≥2 while symptomatic knee OA (SOA) was defined as knee symptoms of at least 1 month in a knee with ROA. Muslims had on average a higher number of daily religious practices than their Buddhist neighbors (p<0.001). The prevalence of knee pain and ROA was significantly higher in Buddhists than in Muslims (67.11 vs. 55.80, p=0.02 for knee pain; 85.62 vs. 70.67, p=0.02 for ROA). For SOA, Buddhists showed a trend towards higher prevalence than Muslims (47.71 vs. 37.32, p=0.068). No significant difference was found when the range of motion and WOMAC scores were compared between the two groups. Muslims had a lower prevalence of OA than their Buddhists counterparts with the same ethnicity but different religious practice. The Muslim way of praying since childhood, forcing the knees into deep flexion, may stretch the soft tissue surrounding the knee and decrease stiffness and contact pressure of the articular cartilage. © 2009 Clinical Rheumatology.